PENGARUH MODEL PEMBELAJARAN SCIENCE, ENVIRONMENT, TECHNOLOGY, AND SOCIETY (SETS) BERBANTUAN MEDIA AUGMENTED REALITY (AR) TERHADAP PEMAHAMAN KONSEP IPAS PESERTA DIDIK KELAS V MIN 10 BANDAR LAMPUNG - Tania Fetri Anjani; Nurul Hidayah; Hasan Sastra Negara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is based on the understanding of the concept of science students Class V MIN 10 Bandar Lampung which is still relatively low. The purpose of this study was to determine whether there is a significant influence on the learning model of Science, Environment, Technology, and Society (SETS) assisted by Augmented Reality (AR) media has an effect on the concept of understanding science students Class V MIN 10 Bandarlampung. The type of research used is quantitative research with quasi Experiment design and using Nonequivalent Control Group Design approach. The sampling technique used is simple random sampling. data collection techniques used are pretest and posttest. The population in this study is all students of Class V MIN 10 Bandar Lampung. The samples in this study are 42 students consisting of 21 students of class VD as an experimental class and 21 students of class VE as a control class. While data analysis techniques using normality test using shapiro wilk test, homogeneity test using fisher test or F test,and hypothesis test in the form of independent sample t-test. The results showed that the test results of the independent sample t-test known significance value (2-tailed) in the analysis of the Test Test independent Sample T-test of 0.000 through the test criteria if the value of significance (2-tailed) < 0.05 then rejected and if the value of significance (2-tailed) > 0.05 then accepted. It turns out that the significance value is 0.000 < 0.05 so is rejected and is accepted. Thus, the hypothesis of this study is accepted, that there is an influence of Learning model Science, Environment, Technology, and Society (SETS) assisted by Augmented Reality (AR) media on the understanding of the concept of science students Class V MIN 10 Bandar Lampung.